2009
DOI: 10.1016/j.vetpar.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of a candidate gene array to delineate gene expression patterns in cattle selected for resistance or susceptibility to intestinal nematodes

Abstract: In the present study, we use microarray technology to investigate the expression patterns of 381 genes with known association to host immune responses. Hybridization targets were derived from previously characterized bovine cDNAs. A total of 576 reporters (473 sequence-validated cDNAs and 77 controls) were spotted onto glass slides in two sets of four replicates. Two color, comparative hybridizations across both mesenteric lymph node (MLN) and small intestine mucosa (SIM) RNA samples were done between animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
1
33
0
2
Order By: Relevance
“…First, Araujo et al (2009) used an immune pathway-focused cDNA array to compare gene expression in mesenteric lymph node and small intestinal mucosa of the selected groups after an exposure to Ostertagia, Cooperia and Nematodirus spp. Results indicated differential expression in both tissues in several functional classes of genes between the resistant and susceptible animals including transcripts encoding immunoglobulin (Ig) chains, integrins such as ITGA4, antigen presentation molecules such as CD45 and CD3E, tissue factors including DMBT1, PGA@, FGFR2 and TUBA2 and proinflammatory cytokine modulators of tumor necrosis factor and interferon.…”
Section: Connor LI Baldwin and Limentioning
confidence: 99%
“…First, Araujo et al (2009) used an immune pathway-focused cDNA array to compare gene expression in mesenteric lymph node and small intestinal mucosa of the selected groups after an exposure to Ostertagia, Cooperia and Nematodirus spp. Results indicated differential expression in both tissues in several functional classes of genes between the resistant and susceptible animals including transcripts encoding immunoglobulin (Ig) chains, integrins such as ITGA4, antigen presentation molecules such as CD45 and CD3E, tissue factors including DMBT1, PGA@, FGFR2 and TUBA2 and proinflammatory cytokine modulators of tumor necrosis factor and interferon.…”
Section: Connor LI Baldwin and Limentioning
confidence: 99%
“…To understand the gene expression-based host responses, messenger RNA (mRNA) expression levels of 381 selected immune-related genes were compared using a candidate gene microarray in this Angus population (Araujo et al 2009). A total of 138 differentially expressed genes (DEGs) were identified, distributing across multiple immune response pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies in phenotypes that are resistant and susceptible to helminth infection have primarily been conducted in sheep, cattle, and rodent models; however, the results are difficult to compare for a number of reasons, e.g., different tissues examined (mucosa, lymph nodes), infection with different parasite species, use of different gene expression platforms (microarray, qPCR), or use of host animals that cannot easily be compared between studies. As an example, some use different breeds or rodent strains whereas others compare resistant and susceptible lines from resource flocks developed by selection and assortative mating for several generations (Pernthaner et al 2005;Ingham et al 2008), or measure gene expression in the most resistant and susceptible animals in a flock after trickle or natural infection (Araujo et al 2009;Zaros et al 2010;Gossner et al 2012;2013). Nevertheless, ovine studies using lymph nodes or lymph cells have found an increased expression of IL-13 but not IL-4 in resistant animals compared to susceptible animals (Pernthaner et al 2005;Gossner et al 2013).…”
Section: Disscussionmentioning
confidence: 99%
“…A similar pattern has been found in sheep (Pernthaner et al 2005;Gossner et al 2013) and cattle (Zaros et al 2010) though not always as pronounced as in murine models. Indeed, the use of new molecular tools which allow the expression of a high number of genes and proteins to be profiled simultaneously (e.g., microarray, microfluidic dynamic arrays, protein arrays) has revealed a much more complex picture than previously expected (Ingham et al 2008;Araujo et al 2009;Andronicos et al 2010).…”
Section: Introductionmentioning
confidence: 99%